Comparative Analysis of Forensic Software on Android-based Blackberry Messenger using NIJ Framework - Imam Riadi; Sunardi Sunardi; Arizona Firdonsyah (IAES Indonesia Section, 2018)
Instant Messaging application is the most widely used application all over the world. Blackberry Messenger is a multiplatform instant messaging with lots of features that can be a magnet for many people to use Blackberry Messenger for commiting digital crimes. In the process of investigating digital crime cases, digital evidences are required. To obtain digital evidence, a set of forensic tools are needed to conduct forensic process on physical evidences. The topic of this research is to describe the forensic process and to compare the current forensic tools used based on acquired digital evidences by using method that refers to mobile device forensic guidelines made by the National Institute of Justice (NIJ). The forensic tools used in this research are Magnet AXIOM, Belkasoft Evidence Center, and MOBILedit Forensic Express. The outcome shows that Magnet AXIOM has the highest capability to obtain digital evidences, Belkasoft Evidence Center has superiority in terms of data text acquisition, and MOBILedit Forensic Express has superiority in physical evidence preserving and cloning.